Dribble deficit as an effective measure of dribbling ability independent of sprinting performance in professional female handball players - Pavlović, Ljubomir; Lazić, Anja; Čović, Nedim; Pišot, Rado; Petronijević, Milan; Milanović, Zoran (Frontiers in Physiology, 2025)
PurposeThe purpose of this study was to determine the relationship between linear and change-of-direction sprinting performance with dribbling performance and Dribble Deficit in professional female handball players.MethodsEleven professional female handball players (mean age: 21.12 ± 4.34 years; body height: 171.59 ± 4.52 cm; body weight: 66.29 ± 5.73 kg) participated in the study. Each participant completed several linear (sprint over 10, 20, and 30 m) and change-of-direction tests (slalom test, zig-zag test, 505 test), first without the ball (sprinting performance) followed by ball dribbling (dribbling performance). Dribble Deficit was calculated indirectly as the time difference between the best trial while dribbling minus the best trial without dribbling.ResultsA large to very large correlation was observed between the linear sprint and dribbling performance (r = 0.53–0.78), as well as between change-of-direction sprinting performance and dribbling performance (r = 0.66–0.88). The study also showed a moderate to perfect relationship between linear dribbling performance and Dribble Deficit (r = 0.46–0.93), and a large relationship between change-of-direction dribbling performance and Dribble Deficit (r = 0.54–0.55), while the relationships between linear sprinting performance and Dribble Deficit (r = −0.51–0.21) and between change-of-direction sprinting performance and Dribble Deficit (r = −0.14–0.26) were small and non-significant.ConclusionIn summary, Dribble Deficit reflects dribbling ability independent of sprinting ability and refines its application for practical use in assessing dribbling skills in female handball players.